Peran Kepolisian Dalam Meminimalisir Kekerasan Seksual Studi Kasus Polres Gorontalo - Andi Esse Jumriani; Sri Rahayu Lestari; Halisma Amili; Agustina Gubali; Yeti S. Hasan (Fakultas Tarbiyah dan Ilmu Keguruan, IAI Sultan Muhammad Syafiuddin, 2024)
Sexual violence in Gorontalo Province itself, especially Gorontalo District, from January to December 2019 there were 16 cases of sexual violence against children handled by the Gorontalo Police PPA Unit. This increase in cases is based on various factors. He further revealed that the majority of perpetrators of sexual violence were committed by people closest to the victim, such as uncles, neighbors, relatives and even stepfathers (continued), even biological fathers, the motives were varied, some were due to persuasion, coercion and seduction by lured by money. Meanwhile, legal protection for child victims of sexual violence is still not optimal, for example in terms of treatment which is considered slow, especially in terms of psychological and social treatment. So the protection rights of children who are victims of sexual violence are still lacking. This research aims to determine the efforts made by the Gorontalo Police to overcome and minimize the occurrence of sexual violence against children. This research uses empirical legal research methods, where the author makes direct observations at the interview location with the parties concerned, namely the head of the PPA unit, one person and the head of the police. This research shows that efforts to overcome crime, especially sexual violence against children in Gororntalo Regency, are preventive efforts, namely prevention efforts carried out by the police such as socialization and counseling and repressive efforts are handling efforts carried out if cases of sexual violence against children have occurred by carrying out rehabilitation for the victims. and detention of the perpetrator. Based on the results of research and analysis, the author recommends that: Gorontalo Police PPA Unit is expected to maintain its performance so that children who are victims of sexual violence receive effective protection and to further increase outreach to the community and law enforcement officials regarding cases of sexual violence against children and provide counseling or socialization by law enforcers which is carried out regularly and on target.